Early Life Experience Shapes Male Behavior and Social Networks in Drosophila - Bentzur, Assa; Ben-Shaanan, Shir; Benichou, Jennifer I C; Costi, Eliezer; Levi, Mali; Ilany, Amiyaal; Shohat-Ophir, Galit (Current biology, 2021)
Living in a group creates a complex and dynamic environment in which behavior of individuals is influenced by and affects the behavior of others. Although social interaction and group living are fundamental adaptations exhibited by many organisms, little is known about how prior social experience, internal states, and group composition shape behavior in groups. Here, we present an analytical framework for studying the interplay between social experience and group interaction in Drosophila melanogaster. We simplified the complexity of interactions in a group using a series of experiments in which we controlled the social experience and motivational states of individuals to compare behavioral patterns and social networks of groups under different conditions. We show that social enrichment promotes the formation of distinct group structure that is characterized by high network modularity, high inter-individual and inter-group variance, high inter-individual coordination, and stable social clusters. Using environmental and genetic manipulations, we show that visual cues and cVA-sensing neurons are necessary for the expression of social interaction and network structure in groups. Finally, we explored the formation of group behavior and structure in heterogenous groups composed of flies with distinct internal states and documented emergent structures that are beyond the sum of the individuals that constitute it. Our results demonstrate that fruit flies exhibit complex and dynamic social structures that are modulated by the experience and composition of different individuals within the group. This paves the path for using simple model organisms to dissect the neurobiology of behavior in complex social environments.